Hitler Stalin pacts reasons and consequeses - Tauber, Joachim (Genocidas ir rezistencija, 2000)
The 23 August 1999 marks the 60th anniversary of the signing of the treaty between National Socialist Germany and the Stalin–ruled Soviet Union. This treaty is of great importance in the discussion of what led to the outbreak of the Second World War. These preconditions leading to the war are what we want to focus on from the perspective of sixty years. What led to those ‘crucial’ political decisions and to the convergence of the positions of the ‘mortal enemies’; at the same time, we will consider the motives of both governments, or their leaders, Hitler and Stalin.